2020
DOI: 10.1098/rspb.2020.1876
|View full text |Cite
|
Sign up to set email alerts
|

Development time mediates the effect of larval diet on ageing and mating success of male antler flies in the wild

Abstract: High-quality developmental environments often improve individual performance into adulthood, but allocating toward early life traits, such as growth, development rate and reproduction, may lead to trade-offs with late-life performance. It is, therefore, uncertain how a rich developmental environment will affect the ageing process (senescence), particularly in wild insects. To investigate the effects of early life environmental quality on insect life-history traits, including senescence, we reared larval antler… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
1
9
2
Order By: Relevance
“…Bees reared on the high carbohydrate diet, the best for survival, also took significantly longer to emerge as adults compared with bees in all other diet groups. This contrasts with previous studies in insects which have typically observed slower development on lower quality diets (Angell et al, 2020;Johnson et al, 1992).…”
Section: Discussioncontrasting
confidence: 99%
“…Bees reared on the high carbohydrate diet, the best for survival, also took significantly longer to emerge as adults compared with bees in all other diet groups. This contrasts with previous studies in insects which have typically observed slower development on lower quality diets (Angell et al, 2020;Johnson et al, 1992).…”
Section: Discussioncontrasting
confidence: 99%
“…Bees reared on the high carbohydrate diet, the best for survival, also took significantly longer to emerge as adults compared to bees in all other diet groups. This contrasts with previous studies in insects which have typically observed slower development on lower quality diets (Johnson, Wofford and Whitehand, 1992; Angell et al ., 2020). For example, Rodrigues et al .…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, considering the fact that females reared at 85% RH during their larval stages were also those that lived the longest, were the largest, and laid more eggs (see below), they may benefit from a "silver spoon" effect, where individuals born in good conditions have fitness advantages later in life (Grafen, 1988;Lindström, 1999;Monaghan, 2008). Such an effect has already been observed-not consistent with all life-history traits, howeverin an experimental study manipulating larval diet in an insect (Angell et al, 2020). Alternatively, high environmental relative humidity may represent cues for a harsher environment, The reproductive senescence was estimated as the ratio of the difference between the two reproductive episodes (early and late) over the total of eggs laid during both reproductive episodes.…”
Section: Does Increasing Growth Rate Ofmentioning
confidence: 99%
“…However, the incomplete knowledge of the environmental conditions experienced early in life by the two ecotypes and the fact that snakes are growing continuously may have prevented the evidence of such a trade-off. In another study, the growth rate of males of the antler fly, Protopiophila litigata, was altered by the experimental manipulation of the larval diet, generating variation in development time, which was positively correlated with lifetime mating rate but not with reproductive senescence (Angell et al, 2020). As a result, more research is needed into the early-late trade-off between growth rate and early reproductive success, as well as their respective impacts on late-life reproductive success and senescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation